(untitled) (The International Research Journal of Management Science, 2017)
The aim of this study is to examine the effect of bonus issue on the price of equity share. The study is based on pooled cross-sectional data of 10 commercial banks whose stocks are listed in NEPSE and traded over the market. An attempt has been made in this study, to analyze the behaviour of the share prices in the Nepalese equity market towards the announcements of bonus issue, taking into account the price movements of the stocks listed in NEPSE. In order to assess the stock price reactions to bonus issue in the Nepalese equity market, Wilcoxon Matched Pairs Test has been applied in this study. The research has revealed that there is a significant impact on the price movement of shares in accordance with the bonus issue in the Nepalese equity market which is consistent to other foremost global equity markets.